Implementasi Bauran Promosi Terhadap Produk Yokito Food - Welly Edta Adzkia; Haryeni (Jurnal Ekonomi dan Bisnis Digital, 2022)
Yokito Food is an online business engaged in cakes and food. The way of promoting their products is very attractive and dominates the market in the current era. The implementation of Yokito Food's product promotion mix is carried out through several strategic steps. The purpose of this paper is (1) to find out how the promotion mix is applied to yokito food products in order to survive in an era of intense competition, (2) to find out which social media is more effective in attracting consumer interest. customer attention. The methods used are library visits, interviews and direct involvement in this online business. The results of this final project show that promotions on Instagram social media are more effective because the features are attractive and easy to access.